Leaky Gut and Mycotoxins: Aflatoxin B1 Does Not Increase Gut Permeability in Broiler Chickens - Galarza-Seeber, Rosario; Latorre, Juan D.; Bielke, Lisa R.; Kuttappan, Vivek A.; Wolfenden, Amanda D.; Hernandez-Velasco, Xochitl; Merino-Guzman, Ruben; Vicente, Jose L.; Donoghue, Annie; Cross, David; Hargis, Billy M.; Tellez, Guillermo (Frontiers in Veterinary Science, 2016)
Previous studies conducted in our laboratory have demonstrated that intestinal barrier function can be adversely affected by diet ingredients or feed restriction, resulting in increased intestinal inflammation-associated permeability. Two experiments were conducted in broilers to evaluate the effect of 3 concentrations of Aflatoxin B1 (AFB1; 2, 1.5 or 1 ppm) on gastrointestinal leakage and liver bacterial translocation (BT). In Exp 1, 240 day-of-hatch male broilers were allocated in two groups, each group had six replicates of 20 chickens (n = 120/group): Control feed or feed + 2 ppm AFB1. In Exp 2, 240 day-of-hatch male broilers were allocated in three groups, each group had 5 replicates of 16 chickens (n = 80/group): Control feed; feed + 1 ppm AFB1; or feed + 1.5 ppm AFB1. In both experiments, chickens were fed starter (d1-d7) and grower diets (d8-d21) ad libitum and performance parameters were evaluated every week. At day 21, all chicks received an oral gavage dose of FITC-d (4.16 mg/kg) 2.5h before collecting blood samples to evaluate gastrointestinal leakage of FITC-d. In Exp 2 a hematologic analysis was also performed. Liver sections were aseptically collected and cultured using TSA plates to determine BT. Cecal contents were collected to determine total cfu/g of Gram-negative bacteria; lactic acid bacteria (LAB) or anaerobes by plating on selective media. In Exp 2, liver, spleen and bursa of Fabricius were removed to determine organ weight ratio, and also intestinal samples were obtained for morphometric analysis. Performance parameters, organ weight ratio and morphometric measurements were significantly different between control and AFB1 groups in both experiments. Gut leakage of FITC-d was not affected by the three concentrations of AFB1 evaluated (P > 0.05). Interestingly, a significant reduction in BT was observed in chickens that received 2 and 1 ppm AFB1. An increase (P < 0.05) in total aerobic bacteria, total Gram negatives, and total LAB were observed in chickens fed 2 and 1.5 ppm of AFB1 when compared with control and 1 ppm chickens. The integrity of gut epithelial barrier was not compromised after exposure to the mycotoxin.